PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SOSIOLOGI SISWA KELAS X IPS 1 DI SMA NEGERI 1 DEPOK-SLEMAN - Nugroho, Dwi; Nurrita, Teni (Moderation | Journal of Islamic Studies Review, 2023)
Social behavior is human behavior and social institutions. The purpose of this research is tofind out the application of the learning model. Project Based Learning and Sociology learning outcomes forclass X IPS 1 SMA Negeri 1 Depok in 2022/2023. The research was conducted using the ClassroomAction Research (CAR) method in 2 cycles. Each cycle consists of planning, implementing, observing andreflecting. The subjects of this study were students of Class X IPS 1 at SMA Negeri 1 Depok. The resultsshowed: 1) Project Based Learning learning syntax was fully implemented. 2) Student learning outcomeswith KKM scores of 75 in the cognitive aspect have increased after using the project based learning model,namely obtaining 63.8% completeness in cycle I to 88.8% in cycle II. 3) The average value of studentlearning outcomes in cycle 1 was 70.28, which increased in cycle II, which was 88.8. 4) The Project BasedLearning learning model can be applied by teachers in Sociology subjects because it improves student learningoutcomes. Based on the results of the research and data analysis conducted, it can be concluded that theapplication of the project based learning model can improve student learning outcomes in class X IPS 1 atSMA 1 Depok for sociology subjects with material regarding the function of sociology to recognize socialphenomena in society in the 2022/2023 school year.